Collateral Projections from the Lateral Parabrachial Nucleus to the Central Amygdaloid Nucleus and the Ventral Tegmental Area in the Rat. Issue 7 (22nd November 2018) - Qiao, Yu; Zhang, Chun‐Kui; Li, Zhi‐Hong; Niu, Ze‐Hao; Li, Jin; Li, Jin‐Lian
ABSTRACT: Lateral parabrachial nucleus (LPB) is a critical region in the integration and transmission of peripheral nociceptive information. The parabrachio‐amygdaloid (P‐Amy) pathway and parabrachio‐ventral tegmental area (P‐VTA) pathway is thought to be significant in regulation of pain‐related negative emotions. In present study, retrograde tract tracers Fluoro‐gold (FG) and tetramethylrhodramine‐dextran (TMR) were stereotaxically injected into the right central amygdaloid nucleus (CeA) and right VTA, respectively. Then, part of these rats were performed with the spare nerve injury (SNI) in the controlateral side of FG and TMR injection. Afterwards, double‐ or triple‐immunofluorescent histochemistry was used to examine FG/TMR double‐ and FG/TMR/FOS or FG/TMR/CGRP triple‐labeled neurons in the LPB. The results showed that all of FG, TMR single‐ and FG/TMR double‐labeled neurons were distributed in the LPB bilaterally with an ipsilateral predominance. The proportion of FG/TMR double‐labeled neurons to the total number of FG‐ and TMR‐labeled neurons was 10.78% and 13.07%, respectively. Nearly all of the FG/TMR double‐labeled neurons (92.67%) showed calcitonin gene‐related peptide (CGRP) immunopositive. On the other hand, in the SNI rats, about 89.49% and 77.87% of FG‐ and TMR‐labeled neurons were FG/FOS‐ and TMR/FOS‐positive neurons; about 93.33% of the FG/TMR double‐labeled neurons were FOS‐LI. Our results suggest that the part of CGRP immunopositive neurons in the LPB send projection fibers to both the CeA and VTA by the way of axon collaterals, which are activated by the nociceptive stimulation in the SNI condition, and may play an important role in the transmission of peripheral nociceptive information. Anat Rec, 302:1178–1186, 2019. © 2018 The Authors. The Anatomical Record published by Wiley Periodicals, Inc. on behalf of American Association of Anatomists.